183k views
3 votes
If r(x) = 3x – 1 and s(x) = 2x + 1, which expression is equivalent to (StartFraction r Over s EndFraction) (6)?

2 Answers

5 votes

Answer:

A on Edge 2021

Explanation:

User Dustin Cowles
by
5.5k points
3 votes

Answer:


(r)/(s)(6)=(3(6)-1)/(2(6)+1)

Explanation:

We know that for any two function f(x) and g(x) ,


(f)/(g)(x)=(f(x))/(g(x))

Given functions :
r(x)=3x-1 and
s(x)=2x+1

Then,
(r)/(s)(x)=(r(x))/(s(x))


\Rightarrow\ (r)/(s)(x)=(3x-1)/(2x+1)

At x= 6 , we get


(r)/(s)(6)=(3(6)-1)/(2(6)+1)

The , The expression is equivalent to
(r)/(s)(6)=(3(6)-1)/(2(6)+1)

When we further simplify it , we get
(r)/(s)(6)=(18-1)/(12+1)=(17)/(13)

User Mark Toman
by
5.6k points